Transfer contact and countertransference in the analytic situation and its relationship to eye movement desensitization therapy and reprocessing. - Fatima Nefidsa; Nabil Amraoui (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
All psychological treatments aim to achieve healing and mental health through the establishment of a therapeutic alliance between the patient and the therapist,But this alliance is built on the basis of communication,The school of psychoanalysis is the first psychological school that focused on this issue through its therapeutic techniques, including clairvoyance, the most important of which is conversion and countertransference.         Despite the introduction of this communication channel, modern psychological treatments have developed the latter and used it in a therapeutic situation to achieve therapeutic goals The most important of these is the integrative psychotherapeutic approach, desensitizing eye movements and reprocessing.